OPTIMALISASI PRODUK TEKNOLOGI INFORMASI DAN KOMUNIKASI UNTUK PEMASARAN BISNIS DI KALANGAN SANTRI PONDOK PESANTREN MUSLIMAT NGALIYAN - Farah Amalia; Fita Nurotul Faizah (Universitas Mataram, 2022)
One of the problems faced by santripreneurs in their business is the limited number of customers so that the business cannot develop. This limited number of customers is due to the lack of a broad marketing reach. This limited marketing reach is a result of the technology gap and the inability of the santripreneurs to optimize Information and Communication Technology (ICT) products for business marketing purposes. This community service activity aims to increase the insight, competence and skills of santripreneurs in optimizing ICT products as an effective and efficient marketing medium. The impact to be obtained after this activity is a broad marketing reach as well as a growing and sustainable business. This activity is carried out using the mini survey method, lectures, tutorials, questions and answers and practice. Lectures and questions and answers about the importance of marketing, digital marketing and various marketplaces, while tutorials and practices on how to operate the Canva application to create a more attractive product display. The results of this community service activity include increasing insight, competence and skills. In the practice session, the students were able to create attractive product displays using the Canva application. The students can also make adjustments between the products offered and the various marketplaces that have been described. The students looked enthusiastic, participatory and gave good testimonials and even gave suggestions for the next service agenda. This community service activity has been carried out properly in accordance with the objectives of the activity. This activity has been able to increase the insight, competence and skills of santripreneurs in optimizing ICT products as an effective and efficient marketing medium.